Neonatal pneumonia in a rural primary care hospital in Bangladesh: prevalence, validation of clinical features and their outcome - Uzzaman, Md Nazim; Khan, Md Al Fazal; Ahmed, Tahmeed; Sarker, Mohammad Habibur Rahman; Yeasmin, Sultana; Saqeeb, Kazi Nazmus; Chisti, Mohammod Jobayer (Bangladesh Critical Care Journal, 2016)
Objective: To explore prevalence, validity of associated factors and their outcome of pneumonia in neonates. Methods: We retrospectively enrolled neonates admitted to a rural hospital in Bangladesh from January 2012-December 2014. Those with pneumonia constituted cases (n=142) and randomly selected three folds of cases from those without pneumonia formed the controls (n=426). Pneumonia was diagnosed by hospital physicians based on respiratory difficulty and/or abnormal auscultatory findings in lungs. Result: The deaths were significantly higher among the cases than the controls (p=0.025). In logistic regression analysis, fast breathing, lower chest wall in-drawing, adventitious sound and cough were independently associated with neonatal pneumonia (for all, p<0.01). However, best of all, sensitivity of fast breathing and lower chest wall in-drawing was 94% and 76% and specificity 81% and 82% respectively. Conclusion: The results underscore the importance of adherence to WHO defined clinical signs in diagnosing pneumonia in neonates especially in resource limited settings. Bangladesh Crit Care J September 2016; 4 (2): 74-78